Gating mechanism of the extracellular entry to the lipid pathway in a TMEM16 scramblase - Byoung-Cheol Lee (Nature Portfolio, 2018)
Some TMEM16 family members are Ca2+-dependent phospholipid scramblases, which also mediate non-selective ion transport; however, the mechanism how lipids permeate through the TMEM16 remains poorly understood. Here, the authors combine biochemical assays and simulations to identify the key steps regulating lipid movement through the membrane-exposed groove.